2023
DOI: 10.32604/cmc.2023.032173
|View full text |Cite
|
Sign up to set email alerts
|

Aspect Level Songs Rating Based Upon Reviews in English

Abstract: With the advancements in internet facilities, people are more inclined towards the use of online services. The service providers shelve their items for e-users. These users post their feedbacks, reviews, ratings, etc. after the use of the item. The enormous increase in these reviews has raised the need for an automated system to analyze these reviews to rate these items. Sentiment Analysis (SA) is a technique that performs such decision analysis. This research targets the ranking and rating through sentiment a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 44 publications
(46 reference statements)
0
9
0
Order By: Relevance
“…Decision Trees are simple, interpretable, and can work well in practice, especially for small to medium-sized datasets. But it requires careful tuning and validation to prevent overfitting and instability, and its performance may be limited by its bias toward certain features [34].…”
Section: Decision Tree (Dt)mentioning
confidence: 99%
“…Decision Trees are simple, interpretable, and can work well in practice, especially for small to medium-sized datasets. But it requires careful tuning and validation to prevent overfitting and instability, and its performance may be limited by its bias toward certain features [34].…”
Section: Decision Tree (Dt)mentioning
confidence: 99%
“…Figure 2 describes the evolution of the EHR in blockchain technology [40]. It explains that the data collected from the patient is stored in the EHR on his/her proper visit to his/her doctor/practitioner and further customized by user access.…”
Section: Data Sharingmentioning
confidence: 99%
“…In their system, medical records management is carried out using a digital archive that has access control rights to its owner's information. This is processed by setting up cloud encryption under the chain.Figure2describes the evolution of the EHR in blockchain technology[40]. It explains that the data collected from the patient is stored in the EHR on his/her proper visit to his/her doctor/practitioner and further customized by user access.…”
mentioning
confidence: 99%
“…Husain and Uzuner Applied several Arabic offensive datasets in the AraBERT model. They found that combining data from multiple datasets lowers the model's performance compared to testing it on individual datasets [32].…”
Section: Deep Learning and Bert Based Modelsmentioning
confidence: 99%